Effects of SIO2 nanoparticles on the structure of polyvinylidene fluoride ultrafiltration membrane - Peng, Y.; Ji, S.; Wang, Shaobin; Jiang, Q. (Serials Publications, 2010)
In this paper we describe the process of adding SiO, nanoparticles into a polyvinylidene fluoride (PVDF) casting solution to prepare inorganic-organic hybrid membranes. The hybrid membrane performance was improved compared with that of a pure PVDF membrane. Tests showed that the pure water flux of the membrane was improved without the decrease in the retention rate. The addition of SiO, nanoparticles induced a strong increase in the viscosity and made the casting operation easier. The phase diagram shows that the addition of SiO, nanoparticles decreases the water tolerance of the solution, and thus speeds up the membrane formation process. The DSC curves also revealed that the degree of crystallinity of PVDF has obviously increased in the hybrid membrane.